ABOUT THE PROPERTIES OF NETWORKS (Academicia Globe: Inderscience Research, 2023)
In this paper, we investigate the following (1) the product of cs-networks, the product of cs*-networks is cs*-networks, the image of cs-network by sequence-covering map is cs-network, the image of cs*-network by 1-sequence-covering map is cs*-network, the product of k-networks is a k-network, the image of k-network by compact-covering map is a k-network.